The expression level of chicken telomerase reverse transcriptase in tumors induced by ALV-J is positively correlated with methylation and mutation of its promoter region - Xiang, Yong; Chen, Qinxi; Li, Qingbo; Liang, Canxin; Cao, Weisheng (Veterinary research (Paris), 2022)
Avian leukosis virus subgroup J (ALV-J) can cause neoplastic diseases in poultry and is still widely prevalent in China. Chicken telomerase reverse transcriptase (chTERT) is the core component of telomerase, which is closely related to the occurrence and development of tumors. Our previous studies showed that chTERT is overexpressed in ALV-J tumors, but the mechanism is still not completely clear. Therefore, this study aims to analyze the possible molecular mechanism of chTERT overexpression in ALV-J tumors from the perspective of DNA methylation and promoter mutation. Methylation sequencing of the chTERT amplicon showed that ALV-J replication promoted the methylation level of the chTERT promoter. And the methylation level of the chTERT promoter in ALV-J tumors was significantly higher than that in tumor-adjacent and normal tissues. Compared with the tumor-adjacent and normal tissues, the chTERT promoter in each ALV-J tumors tested had a mutation of −183 bp C > T, and 36.0% (9/25) of the tumors also had mutations of −184 bp T > C, −73 bp::GGCCC and −56 bp A > T in the chTERT promoter, which formed the binding sites for the transcription factors NFAT5, TFAP2A and ZEB1, respectively. The results of RT–qPCR and Western blotting showed that the occurrence of these mutations significantly increased the expression level of chTERT. In conclusion, this study demonstrated that the high expression of chTERT in ALV-J tumors is positively correlated with the level of hypermethylation and mutation in its promoter, which provides a new perspective for further research on the molecular mechanism of chTERT in ALV-J tumorigenesis.